2011
DOI: 10.1002/adsc.201100112
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrole‐Assisted and Easy Oxidation of Cyclic α‐Amino Acid‐ Derived Diketopiperazines under Mild Conditions

Abstract: A new procedure for the aerobic oxidation of a-amino acids acylated by pyrrole-carboxylic acid with triplet dioxygen is introduced. The reaction is general for a variety of pyrrole-amino acid derivatives and represents a very practical and controllable method for the selective preparation of a-hydroperoxy-or a-hydroxy-a-amino acid diketopiperazines with molecular dioxygen. Furthermore, the non-catalyzed direct oxidation of amino acid derivatives at the a-position with molecular dioxygen represents a fundamenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…For known compounds 3a-b, g, m-n only 1 H and 13 C NMR are reported. 44,45 Methyl Isolates are kept frozen at -80°C in 17% glycerol solution in the laboratory collection of the microbiology section of the Department of Pharmaceutical Sciences, University of Perugia (Italy). Short term storage was carried out at 4°C on YEPDA (YEPD added with 1.7% agarose).…”
Section: Methodsmentioning
confidence: 99%
“…For known compounds 3a-b, g, m-n only 1 H and 13 C NMR are reported. 44,45 Methyl Isolates are kept frozen at -80°C in 17% glycerol solution in the laboratory collection of the microbiology section of the Department of Pharmaceutical Sciences, University of Perugia (Italy). Short term storage was carried out at 4°C on YEPDA (YEPD added with 1.7% agarose).…”
Section: Methodsmentioning
confidence: 99%
“…Amides 37, resulting from the condensation of 2-trichloroacetylpyrrole (or pyrrole-2carboxylic acid and amidation reagents) and different amino esters derived from natural amino acids (shown here for proline), were cyclized with sodium hydride in THF to the diketopiperazine derivatives 38 in high yield. Several reports have appeared in the literature [59,[61][62][63][64]. These compounds 38 could be oxygenated with molecular oxygen to a hydroperoxide and could be reduced in situ with dibutyl sulfide ((n-Bu) 2 S) or triphenyl phosphine (PPh 3 ), affording the hydroxy product 39 in high yield [62] (Scheme 10).…”
Section: Scheme 9 Cyclization Of Prolinol Derivativesmentioning
confidence: 99%
“…Several reports have appeared in the literature [59,[61][62][63][64]. These compounds 38 could be oxygenated with molecular oxygen to a hydroperoxide and could be reduced in situ with dibutyl sulfide ((n-Bu) 2 S) or triphenyl phosphine (PPh 3 ), affording the hydroxy product 39 in high yield [62] (Scheme 10). Recently, it was found that these diketopiperazines 38 could function as catalysts in oxygenation reactions [65], and the oxygenation of compound 38 in the presence of guanidine has also been mentioned as acting in the biogenesis of 2-aminoimidazolidinone metabolites from sponges [61].…”
Section: Scheme 9 Cyclization Of Prolinol Derivativesmentioning
confidence: 99%
“…There are both R Compound 277 [233] (Figure 79) has two linear parallel chains of molecules linked to each other by interactions of one imide CO of each molecule to both the imide NH of one molecule in the opposite chain and an alcohol OH of an adjacent molecule also in the opposite chain. In this way each molecule has two donor and two acceptor interactions and is involved in two R Compound 276 [231,232] (Figure 78) exists in a complex pattern of hydrogen bonding.…”
Section: Bridged Six-membered Ring Imidesmentioning
confidence: 99%
“…There are both R Compound 277 [233] (Figure 79) has two linear parallel chains of molecules linked to each other by interactions of one imide CO of each molecule to both the imide NH of one molecule in the opposite chain and an alcohol OH of an adjacent molecule also in the opposite chain. In this way each molecule has two donor and two acceptor interactions and is involved in two R Compound 277 [233] (Figure 79) has two linear parallel chains of molecules linked to each other by interactions of one imide CO of each molecule to both the imide NH of one molecule in the opposite chain and an alcohol OH of an adjacent molecule also in the opposite chain. In this way each molecule has two donor and two acceptor interactions and is involved in two R 2 2 (9) units, one as the four atom component and one as the five atom component and the two enantiomeric chains are strongly bound into a ribbon structure.…”
Section: Bridged Six-membered Ring Imidesmentioning
confidence: 99%